Performance of Semi-Micro-Kjeldahl Nitrogen Method – uncertainty and nitrate interference. Issue 18 (28th December 2022) - Trikilidou, Eleni; Samiotis, Georgios; Tsikritzis, Lazaros; Amanatidou, Elisavet
ABSTRACT: Semi-Micro-Kjeldahl method is a TKN analysis method included in Standard Methods for the Examination of Water & Wastewater, but no data on its trueness and precision are available. The method itself has inherent limitations and principal interferences, negative or positive, provoked from high nitrate concentrations. In this work, Semi-Micro-Kjeldahl method performance and nitrate interference were studied. Trueness, precision under repeatability conditions, intermediate precision, limit of quantification, recovery and measurement uncertainty, were calculated with satisfactory results. The Lower Laboratory Limit of Quantification was determined at 2 mg L −1 TKN concentration; lower than 4 mg L −1 proposed by standard methods. Nitrogen digestion recovery (nicotinic acid spiking solution) and nitrogen loss (ammonium chloride spiking solution), ranged from 92% to 98% and from 92% to 104% respectively and were in the general acceptable limits (90%–110%) and in the nutrients acceptable limits (80%–120%). The results of the inter-laboratory measurements confirmed the assumptions taken and verified the calculations of measurement uncertainty. Nitrate concentration limit over which negative and positive interference is significant was quantified at 400 mg L −1 . Consequently, as this study demonstrates, the Semi-Micro-Kjeldahl method is applicable for the majority of water and wastewater samples.